Pengaruh Pengetahuan Akuntansi Lingkungan, Kepekaan Lingkungan, dan Pengetahuan CSR Terhadap Perilaku Keberlanjutan Lingkungan Mahasiswa Akuntansi - Septian Nur Alam; Dian Efriyenti (Economic Reviews Journal, 2026)
Environmental sustainability awareness has become a crucial concern in higher education, particularly for accounting students who are expected to serve as future professionals in economic and business decision-making. This study aims to examine the effects of environmental accounting knowledge, environmental sensitivity, and Corporate Social Responsibility (CSR) knowledge on the environmental sustainability behavior of accounting students. A quantitative research design employing a survey method was adopted. Data were collected through structured questionnaires distributed to 206 active accounting students. The data were analyzed using descriptive statistics, classical assumption tests, multiple linear regression analysis, and hypothesis testing through t-tests and F-tests. The results indicate that environmental accounting knowledge, environmental sensitivity, and CSR knowledge each have a positive and statistically significant effect on environmental sustainability behavior. Simultaneously, these independent variables collectively demonstrate a significant influence on such behavior. Among the variables examined, environmental sensitivity shows the most dominant effect. These findings suggest that enhancing students’ environmental awareness and knowledge particularly through environmental accounting and CSR education plays an essential role in fostering environmentally responsible behavior. This study is expected to provide valuable insights for higher education institutions in curriculum development and to serve as a reference for future research on environmental sustainability behavior.